2018
DOI: 10.3389/fmicb.2018.01890
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic Induction Greatly Enhances Leishmania major Intracellular Survival Compared to Leishmania amazonensis in CBA/j-Infected Macrophages

Abstract: CBA mouse macrophages control Leishmania major infection yet are permissive to Leishmania amazonensis. Few studies have been conducted to assess the role played by autophagy in Leishmania infection. Therefore, we assessed whether the autophagic response of infected macrophages may account for the differential behavior of these two parasite strains. After 24 h of infection, the LC3-II/Act ratio increased in both L. amazonensis- and L. major-infected macrophages compared to uninfected controls, but less than in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 60 publications
5
29
0
1
Order By: Relevance
“…Although Leishmania parasite-induced autophagy in neutrophils has not been demonstrated, multiple reports confirm macrophage autophagy upon Leishmania infection (51)(52)(53) The observed increase in hPMN autophagy postinfection with the Leishmania parasites is in line with reports of autophagy induction by other classes of pathogens (5,54). To explore the functional role of autophagy, it was important to establish the kinetics of the process in hPMNs.…”
Section: Discussionsupporting
confidence: 55%
“…Although Leishmania parasite-induced autophagy in neutrophils has not been demonstrated, multiple reports confirm macrophage autophagy upon Leishmania infection (51)(52)(53) The observed increase in hPMN autophagy postinfection with the Leishmania parasites is in line with reports of autophagy induction by other classes of pathogens (5,54). To explore the functional role of autophagy, it was important to establish the kinetics of the process in hPMNs.…”
Section: Discussionsupporting
confidence: 55%
“…Parasites can incite anti-inflammatory responses and modify antigen presentation by deregulating the host's autophagy machinery via mimicking apoptosis signals, such as those known as apoptotic-like Leishmania, and reducing the proliferation of CD4 T cells [86,87]. The miRNAs miR-101c, miR-129-5p, miR-155, and miR-210-5p, which are differentially expressed in L. major-infected BMDM, were related to the activation of the autophagic machinery and interfere with parasite clearance [56].…”
Section: Leishmania-host Interactionsmentioning
confidence: 99%
“…The close relationship between oxidative stress and the autophagic process has been shown by evidence from many authors (Lee et al, 2012). The NO burst production in L. amazonensis and L. major infections was reduced by autophagy induction without causing changes to arginase activity (Dias et al, 2018). As L. amazonensis infection is able to induce autophagy, which is essential for the progression of the infection (Pinheiro et al, 2009), and the participation of the Nrf2, PKR, and PI3K pathways has been reported in this cellular process; that is, there is a close relationship or convergence of these signaling pathways such that, together, they may trigger autophagy and the creation of an antioxidative profile during L. amazonensis infection.…”
Section: Nrf2 Pathway In Leishmania Infectionmentioning
confidence: 67%